The Inner Nana, the List Mum and Me:: Knitting Identity - Minahan, Stella; Cox, Julie (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract Here we present young knitters’ reflections on their acquisition of textile skills and we review media images of women and knitting. While the image of the grandmother as teacher is clear, the mother is absent or obscure. This absence is also reflected in knitting groups, blogs and in one of the authors’ false memories. We propose further investigation of the construction of identity through craft and of both the materiality and the ethereality of nostalgic references.